An analysis of neoliberal small entrepreneurship through the concepts of hegemony and governmentality - Ayla Ezgi Akyol (Trakya Üniversitesi İktisadi ve İdari Bilimler Fakültesi E-Dergi, 2022)
The rise of small-sized enterprises, which was prompted by a change in the regime of accumulation in late capitalism, heralds not only the emergence of a new form of business management that increases the efficiency of production, but also the birth of a new form of subjectivity. Situated within capitalist social relations, small-sized enterprises play an important role both in facilitating the control of labor power and in abstracting labor from its social content to define it at the individual level according to the singular qualities of subjects. In this article, small-sized enterprises and the ideological determinations and technologies of power underlying them are discussed in relation to Michael Foucault’s concept of “governmentality” and Antonio Gramsci’s concept of “hegemony”. It is argued that small-sized enterprises essentially serve to socialize the logic of “entrepreneurship”, one of the main instruments of power of neoliberalism, through both the conduct of conduct as Foucault states and the articulation of common sense in the context of Gramsci’s conceptualization.